2011
DOI: 10.1007/s10563-011-9116-x
|View full text |Cite
|
Sign up to set email alerts
|

(Imido)vanadium Complexes as Efficient Catalyst Precursors for Olefin Polymerization/Oligomerization

Abstract: Arylimido)vanadium(V) complexes containing anionic ancillary donor ligands of type, V(NAr)Cl 2 (L) (Ar = 2,6-Me 2 C 6 H 3 , L = aryloxo, ketimide phenoxyimine, etc.) exhibited high catalytic activities for ethylene polymerization in the presence of Al cocatalyst; V(NAr)Cl 2 (O-2,6-Me 2 C 6 H 3 ) showed the exceptionally high activities in the presence of halogenated Al alkyls such as Et 2 AlCl, EtAlCl 2 , etc. (Arylimido)vanadium(V)-alkylidene complexes, V(CHSiMe 3 ) (NAr)(L 0 ) (L 0 = N=C t Bu 2 , O-2,6-i Pr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…There has been a long-standing interest in metal–ligand multiple bonds involving late 3d transition metals, in particular those compounds containing an imido functionality. Imido ligands can donate up to six electrons by acting as a 2σ, 4π donor ligand. , Furthermore, the imido functionality not only acts as an ancillary ligand in homogeneous catalysis but also acts to actively participate in organic reactions and stabilize highly reactive species. Nevertheless, reactivity always correlates with the electronic structure of the central metal atom.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a long-standing interest in metal–ligand multiple bonds involving late 3d transition metals, in particular those compounds containing an imido functionality. Imido ligands can donate up to six electrons by acting as a 2σ, 4π donor ligand. , Furthermore, the imido functionality not only acts as an ancillary ligand in homogeneous catalysis but also acts to actively participate in organic reactions and stabilize highly reactive species. Nevertheless, reactivity always correlates with the electronic structure of the central metal atom.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh found that the imido vanadium catalyst supported on the SiO 2 with MAO as the co‐catalyst had higher activity than that supported on the other supports. Zhang and Nomura focused on high oxidation state imido vanadium complexes containing anionic ancillary donor ligands because the olefin coordination onto the highest oxidation state vanadium–alkyl complexes would be suitable for the subsequent insertion. Several researchers suggested that the use of vanadium‐based catalysts usually allows the preparation of high‐molecular‐weight polymers with narrow MWD, and ethylene/α‐olefin copolymers with high α‐olefin incorporation …”
Section: Introductionmentioning
confidence: 99%
“…One way to overcome this problem is adding Cl 3 CCOOEt or chlorinated hydrocarbons (viz., “rejuvenators” or “promoters” in the literature), which has proven to be effective reagents for maintaining the higher (active) oxidation state of vanadium systems . The introduction of ancillary ligands is another powerful method of stabilizing the catalytically active species by way of variation of the number, size and electronic properties of ligands . In recent years, great advances in vanadium catalytic systems with improved catalytic activity and thermal stability have been achieved .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Redshaw et al reported various aryloxide‐based vanadium complexes which exhibit excellent performance for ethylene polymerization at an elevated temperature . Golisz and Bercaw discovered that a vanadium (III) complexes containing bis(phenoxy)pyridine ligand showed remarkable catalytic activity for propylene polymerization and afforded high molecular weight polypropylene with uniform weight distributions . Nomura and Zhang obtained series of vanadium (V) imido complexes with aryloxide coligands as efficient catalysts for olefin (co)polymerization, and some systems exhibited remarkable catalytic activities, excellent comonomer incorporation ability at high temperature .…”
Section: Introductionmentioning
confidence: 99%